Variasi Genetik Populasi Monyet Ekor Panjang (Macaca fascicularis) di Pulau Nusa Penida, Klungkung, Bali (GENETIC VARIATION OF LONG TAIL MACAQUE (MACACA FASCICULARIS) POPULATION IN NUSA PENIDA ISLAND, KLUNGKUNG, BALI) - Nugraha, Elisabeth Yulia; Wandia, I Nengah; Soma, I Gede (Jurnal Veteriner; Vol 19 No 4 (2018)DO - 10.19087/jveteriner.2018.19.4.531, 2019)
The purpose of this study is to discover about heterozygosity, migration between populations, and mating habits of Macaca fascicularis among the population in Nusa Penida Island, Klungkung, Bali. Fourteen blood samples from Macaca fascicularis were taken from Nusa Penida Island that consist of eleven samples from Puncak Mundi Temple and three samples from Paluang Temple were used in the study. Samples were extracted using QIAamp DNA Blood Mini Kits produced by Qiagen. Five loci microsatellite (D10S611, D11S1366, D13S765, D17S1290, and D18S536) were amplified using the Polymerase Chain Reaction (PCR) technique. Thirty cycles of PCR were carried out with an annealing temperature of 500C. Alleles were separated by electrophoresis on eight percent polyacrylamide gel and presented with silver staining. The results showed high heterozygosity is 0.762 of Macaca fascicularis populations on Nusa Penida Island with random mating habits. Low genetic differentiation is 0.05. High the number of migrations between populations (genetic flow) of Macaca fascicularis populations on Nusa Penida Island is 4.75 with migration between populations of five individual/generation. Based on the results of the study it was concluded that the genetics of the Macaca fascicularis population on Nusa Penida Island varies.